Synthesis of morphology-controlled silver nanostructures by electrodeposition - Liang, C. L.; Zhong, K.; Liu, M.; Jiang, L.; Liu, S. K.; Xing, D. D.; Li, H. Y.; Na, Y.; Zhao, W. X.; Tong, Y. X.; Liu, P. (Nano-Micro Letters, 2010)
Nanostructured silver was obtained by potentiostatic electrolysis. The effects of ionized surfactant (sodium dodecanesulphonate) and the substrate (Cu and Ti) on the morphology of depositions were investigated. It is found that morphologies of silver nanostructures can be simply controlled via change of the substrate. Spherical Ag nanoparticles with narrow size distribution were obtained by electrodeposition in AgNO3-SDS aqueous solution on copper substrate. In the case of titanium substrate, silver dendrite structures were obtained. Despite of different morphologies, XRD and TEM results showed that the as-prepared samples belong to face-centered cubic silver structure with good crystallinity. The formation mechanism of different silver nanostructures was discussed.